Late Pleistocene fauna from Chongphadae Cave, Hwangju County, Democratic People's Republic of Korea. Issue 1 (September 2020) - Choe, Rye Sun; Han, Kum Sik; Kim, Se Chan; U, Chol; Ho, Chol Ung; Kang, Il
Abstract: We report on a diverse and abundant mammal fauna from Chongphadae Cave—Hwangju region in the Democratic People's Republic of Korea (DPRK). The cave sediments include many mammal fossils and consist of fluvial, cave clay, and calcareous deposits. During our field excavation 33 species were encountered: 9 species of rodents, 1 species of lagomorph, 1 species of insectivore, 8 species of carnivores, 4 species of perissodactyls, 9 species of artiodactyls, and 1 species of primates. Of these, perissodactyls and artiodactyls dominate the fauna in terms of diversity. The cave sediments include 15 layers. Radiocarbon dating showed that Layers 12 and 13 were formed from 34, 770 to 27, 800 cal yr BP and from 24, 980 to 21, 340 cal yr BP, respectively. Additional identification of various palyno-botanical remains including 25 families and genera of trees, 19 families and genera of grasses and herbs, and 10 families and genera of ferns provides a wealth of information on the past ecology of the Chongphadae Cave Site area. During the Late Pleistocene, the Chongphadae area was surrounded by luxuriant forests associated with hills and grasslands in a cool and humid temperate climatic environment.